DIET AND LIFESTYLE FACTORS ASSOCIATED WITH THE RISK OF GALLSTONE DISEASE: A REVIEW OF THE CURRENT LITERATURE - Jakub Hamouta; Wiktor Doroszuk; Dawid Sewruk; Magdalena Próchnicka; Michał Siwek; Natalia Strumnik; Jan Noskowicz; Jan Urban; Kamila Derlatka; Julia Konat (International Journal of Innovative Technologies in Social Science, 2025)
Background: Gallstone disease (GSD) is a prevalent gastrointestinal disorder, particularly in developed countries, with a global adult prevalence ranging between 10% and 20%. Although often asymptomatic, GSD may lead to serious complications including acute pancreatitis, cholecystitis, and biliary obstruction. Aim: This review aims to summarize current evidence on dietary and lifestyle factors associated with the risk of gallstone disease and explore modifiable risk factors relevant for prevention. Material and Methods: A narrative review of recent literature was conducted using peer-reviewed articles published in PubMed and Google Scholar. Prospective cohort studies, meta-analyses, and Mendelian randomization analyses were included to evaluate associations between dietary patterns, lifestyle behaviors, and gallstone disease risk. Results: High intake of ultra-processed foods, sugar-sweetened beverages, and refined carbohydrates was consistently associated with an increased risk of GSD. Conversely, plant-based diets emphasizing whole and minimally processed foods, high fruit and vegetable consumption, and anti-inflammatory dietary patterns showed protective effects. Vegetarian diets appeared particularly beneficial for women. Additionally, obesity, type 2 diabetes, and smoking were confirmed as causal risk factors, while moderate coffee consumption may reduce GSD risk. Rapid weight loss and weight cycling were also identified as risk enhancers. Additionally, increased physical activity appears to reduce the risk of GSD. Conclusions: The findings highlight the importance of dietary quality and healthy lifestyle choices in the prevention of gallstone disease. Modifiable factors such as diet composition, physical activity, and body weight management play a pivotal role in reducing GSD incidence. Preventive strategies should focus on long-term adherence to plant-based, low-processed diets and healthy lifestyle practices.